Multiplying polynomials
Upcoming SlideShare
Loading in...5
×
 

Multiplying polynomials

on

  • 1,795 views

 

Statistics

Views

Total Views
1,795
Views on SlideShare
606
Embed Views
1,189

Actions

Likes
0
Downloads
28
Comments
0

2 Embeds 1,189

http://ncvps.blackboard.com 1176
http://ncvps.blackboard.net 13

Accessibility

Categories

Upload Details

Uploaded via as Microsoft PowerPoint

Usage Rights

© All Rights Reserved

Report content

Flagged as inappropriate Flag as inappropriate
Flag as inappropriate

Select your reason for flagging this presentation as inappropriate.

Cancel
  • Full Name Full Name Comment goes here.
    Are you sure you want to
    Your message goes here
    Processing…
Post Comment
Edit your comment

Multiplying polynomials Multiplying polynomials Presentation Transcript

  • Multiplying Polynomials
    NCVPS
    Summer 2010
  • Multiplying two terms
    Use the product rule to combine exponents:
    x2x3 = x(2 + 3) = x5
    a(2a5) = 2a(1+5) = 2a6
    3x2(2x5) = 3*2x(2+ 5) = 6x7
    Do you see in this last example that the coefficients are multiplied together?
  • Multiplying a Monomial with a Binomial
    A monomial is a single term, such as 2x
    A binomial means there are two terms in the expression. An example is 3x + 1.
    Let’s multiply:
    2x(3x + 1)
    = 2x(3x) + 2x (1) using distributive property
    = 6x2 + 2x
  • You Try One!
    Example 2: 4x(x – 3)
    Click on the slide when ready to move forward!
  • You Try One!
    Example 2: 4x(x – 3)
    4x(x – 3)
    = 4x(x) + 4x(-3)
    = 4x2 + (-12x)
    = 4x2 – 12x
  • Two Binomials Multiplied
    Let’s look at (2x – 3)(x + 4).
    Each term in the first binomial is distributed against the second binomial.
    2x(x+4) + (-3)(x + 4)
    = 2x(x) + 2x(4) + (-3)(x) + (-3)(4)
    = 2x2 + 8x + (-3x) + (-12)
    = 2x2 + 5x - 12
  • You Try One!
    Multiply (5x - 1)(2x + 3). Click on the slide when you are ready!
  • You Try One!
    Multiply: (5x - 1)(2x + 3)
    =(5x)(2x + 3) + (-1)(2x + 3)
    =(5x)(2x) +5x(3) + (-1)(2x) + (-1)(3)
    =10x2 + 15x – 2x – 3
    =10x2 + 13x - 3
  • Are you ready?
    See your teacher if you have further questions!
    Take your formative assessment!